Neuronavigation accuracy of the VOSTARS wearable AR platform vs traditional infrared navigation in a comparative study - Marina Carbone; Nadia Cattari; Fabrizio Cutolo; Martina Autelitano; Emanuele Cigna; Vincenzo Ferrari; Nicola Montemurro; Sara Condino (Scientific Reports)
Abstract Neuronavigation is integral to modern neurosurgery. Clinical studies demonstrate its effectiveness. The primary tracking modalities in neurosurgical navigation are optical tracking systems (OTS) and electromagnetic tracking systems (EMTS). OTS remains the gold standard due to its accuracy and reliability. However, inherent inaccuracies due to brain deformation, image resolution, tool calibration, and registration errors can impact overall accuracy significantly, which differs from the system-declared accuracy. Augmented reality (AR) technologies solve traditional navigation challenges by integrating virtual information with the patient’s anatomy, enhancing the surgeon’s focus and cognitive load management. Head-mounted displays (HMDs) offer ergonomic benefits, although most AR-based neuronavigation studies have been limited to proof-of-concept trials. This study aims to evaluate VOSTARS, a novel hybrid video and optical see-through HMD designed for precision surgery, specifically in neurosurgical oncology for targeting supratentorial tumors. Previous in-vitro studies using patient-specific phantoms have shown promising results, with high accuracy in real-to-virtual target visualization and craniotomy trajectory tracing. With this work, we further assessed VOSTARS’ targeting accuracy within a realistic neurosurgery clinical workflow and compared its performance to the commercial StealthStation system on a patient-specific phantom. Our results demonstrate that users achieved the same median accuracy, 2 mm (IQR: 1 mm), over 60 measurements with both VOSTARS and the StealthStation with no statistically significant difference between the systems, confirming the non-inferiority of the VOSTARS platform compared to a commercial optical tracking-based surgical navigator.